THE ROLE OF STUDENTS' EFFECTIVE LEARNING AND TECHNOLOGICAL SUPPORT ON THE PERCEPTION OF TEACHERS TOWARDS TECHNOLOGY-BASED TEACHING FOR ESL IN CHINA - Saima Javed , Zhang Wenlan , Kamran Ijlal , Uzma Sarwar ,Samina Zamir , Tariq Mehmood Bhuttah (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This study examined the impact of students' effective learning based on technology-based teaching and technological support on the perceptions of teachers regarding technologyintegrated teaching of (ESL) in China through the structural equation model (SEM). This study is based on the collected data obtained through an online questionnaire. The online survey was distributed in several foreign teachers groups on WeChat in China. A total of three hundred and ninety-five foreigners as English teachers filled the questionnaire. The descriptive statistics showed that the number of males as English teachers is higher than females, and 61.6 percent of teachers prefer to use modern teaching methods. Structural Equation Modeling (SEM) revealed that the active learning of students and technological support significantly determine the teachers' perceptions of technology used for teaching the English language.